Heterogeneous impact of crop diversification on farm net returns and risk exposure: Empirical evidence from Ghana - Baba Adam; Awudu Abdulai (Canadian Journal of Agricultural Economics/Revue canadienne d'agroeconomie, 2024)
Abstract Increasing frequency of extreme weather events threatens the livelihoods of low-income farm households due to the heavy dependence on rain-fed agriculture coupled with the under-developed formal markets for risk management products. Thus, crop diversification is one of the widely used ex ante adaptation strategies to hedge against weather risk exposure. In this study, we use survey data from the northern Savanna zone of Ghana merged with historical weather data to shed light on the heterogeneous impact of crop diversification on farm net returns and risk exposure. We employ the dose response function and instrumental variable techniques to address potential endogeneity concerns. Overall, our findings show that crop diversification is a welfare-enhancing strategy that significantly increases farm net returns, lowers the probability of crop failure, and thus decreases downside risk exposure. Notably, our dose-response function analysis demonstrates that the positive benefits of crop diversification are particularly pronounced at lower intensities, reaching an optimal threshold. Beyond this point, the incremental advantages tend to diminish, suggesting the importance of carefully considering the optimal level of diversification for maximum benefits. The results further underscore the significant impact of both access to agricultural extension services and fertilizer usage on the adoption of crop diversification.
Keywords: 330; climate risk management; crop diversification; dose response function